PECULIARITIES OF FINANCIAL PROVISION OF RURAL TERRITORIAL COMMUNITIES IN CONDITIONS OF SUSTAINABLE DEVELOPMENT - PTASHCHENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Financial provision of rural territorial communities in conditions of sustainable development is an important aspect of the country’s economic and social development. The successful functioning and development of such communities depend on their ability to attract and effectively distribute the financial resources needed to improve infrastructure, education, health care and other vital areas. In the conditions of sustainable development, which involves a balance between economic growth, social well-being and environmental protection, the financial support of rural communities becomes especially important for the preservation of their unique natural and cultural heritage. That is why the purpose of the presented work is to determine the features of financial support of rural territorial communities in conditions of sustainable development. The methods that were used in the formation of the current study are: methods of analysis and synthesis to determine the key aspects of the development of rural territorial communities; methods of induction and deduction to determine the features of the financial provision of territories; method of comparison; logical method; graphical and tabular methods for visual display of research results. Also, as a result of the study, it was proved that the necessity of diversifying the sources of financing is a prerequisite for the financial provision of rural territorial communities. In particular, such communities should actively attract local tax revenues, state support, as well as use the opportunities of international grants and technical assistance programs. At the same time, effective management of resources aimed at the implementation of sustainable development programs, which includes energy saving, development of local businesses and support of environmental initiatives, becomes an important task. In the context of reforming the financial system in Ukraine, financial decentralization is of particular importance, which opens up new opportunities for strengthening the financial independence of rural communities, at the same time placing greater responsibility on them for the rational use of funds. Rural communities can direct the received finances to improve infrastructure, develop social services, support local entrepreneurs, as well as to environmental and energy-saving initiatives.